2021
DOI: 10.3390/s21030902
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Polar H7 Heart Rate Sensor for Heart Rate Variability Analysis during Exercise in Different Age, Body Composition and Fitness Level Groups

Abstract: This work aims to validate the Polar H7 heart rate (HR) sensor for heart rate variability (HRV) analysis at rest and during various exercise intensities in a cohort of male volunteers with different age, body composition and fitness level. Cluster analysis was carried out to evaluate how these phenotypic characteristics influenced HR and HRV measurements. For this purpose, sixty-seven volunteers performed a test consisting of the following consecutive segments: sitting rest, three submaximal exercise intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Chest-strap devices use sensors to measure the electric activity of the heart and have been often used as a simple and less costly alternative to traditional ECG. A number of studies that used chest-strap heart-rate devices found that in general, they show excellent agreement during resting and exercise at light to moderate intensities, but some decreased their accuracy during higher exercise intensities, while others maintained an excellent performance even during high-intensity exercise [ 65 , 66 ]. Nonetheless, the overall level of agreement varied among participants, level of exercise, and indices of HRV [ 65 ].…”
Section: Monitoring Cardiac Function and Cardiovascular Healthmentioning
confidence: 99%
“…Chest-strap devices use sensors to measure the electric activity of the heart and have been often used as a simple and less costly alternative to traditional ECG. A number of studies that used chest-strap heart-rate devices found that in general, they show excellent agreement during resting and exercise at light to moderate intensities, but some decreased their accuracy during higher exercise intensities, while others maintained an excellent performance even during high-intensity exercise [ 65 , 66 ]. Nonetheless, the overall level of agreement varied among participants, level of exercise, and indices of HRV [ 65 ].…”
Section: Monitoring Cardiac Function and Cardiovascular Healthmentioning
confidence: 99%
“…However, in the literature, it is controversial whether HRV parameters calculated from time series of RR intervals obtained from ECG recordings and from pulse durations obtained from PPG signals or continuous non-invasive blood pressure monitoring (e.g., Finapress) can be used alternatively [ 54 ]. Nowadays, the number of wearable and telemedical devices that are equipped with either ECG or PPG detectors dynamically increases [ 55 , 56 ]. This may open new prospects for scientists and physicians to exploit the opportunities offered by HRV/PRV analysis in patient evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…More studies have been published recently combining HRV and mHealth technologies [ 63 , 64 , 65 , 66 ]. However, one of the main limitations of those studies is the high sensitivity to the body movement and the presence of artifacts as that most of them rely on a photoplethysmography sensor for detecting the heartbeats or the inter-beat cardiac intervals [ 67 , 68 ]. The gold standard for HRV analysis is based on the lab-ECG signal.…”
Section: Discussionmentioning
confidence: 99%
“…However, this recording method requires the use of electrodes and leads, so it is expensive, uncomfortable for the patient, and requires some training. As an alternative to the lab-ECG, they are recently appearing portable user devices based on mHealth technology, detecting ECG signals deriving the RR interval values for HRV analysis [ 38 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%